Strengthening Children's Islamic Character Through Tahsin, Prayer Memorisation, and Etiquette Education at TPA At-Taqwa Air Tiris - Lubis, Hasan Hamzah; Khairul Anhar; Ritonga, Ade Muhammad; Nurlatifa Zahrah (As-sunnah: Jurnal Pengabdian Masyarakat, 2026)
Non-formal Quranic educational institutions known as Taman Pendidikan Al-Qurʾān (TPA) play a strategic role in cultivating children's Islamic character; however, deficiencies in Quranic recitation proficiency, comprehension of daily supplications, and the practical internalisation of Islamic etiquette remain prevalent challenges in many TPA settings, including TPA At-Taqwa in Kelurahan Air Tiris, Kecamatan Kampar, Kabupaten Kampar, Riau Province. This community service programme aimed to strengthen the Islamic character of children through three integrated activities: Quranic tahsin instruction, daily prayer memorisation, and Islamic etiquette education. The programme was conducted as part of the Thematic Community Field Study (KKNT) of STAI As-Sunnah Deli Serdang in collaboration with TPA At-Taqwa Air Tiris, involving 50 child participants aged six to twelve years over the period of 3 to 17 March 2025. The Asset-Based Community Development (ABCD) approach was employed as the overarching framework, with the talaqqi method applied specifically for Quranic and supplication instruction. The findings indicate that approximately 80 per cent of participants demonstrated measurable improvement in Quranic recitation ability and prayer memorisation, while 70 per cent responded correctly to etiquette-related questions in the evaluation quiz. Children also exhibited positive behavioural changes in daily life, including the spontaneous recitation of appropriate supplications, the correct performance of ritual purification (wuḍūʾ), and the adoption of courteous conduct in social interactions. This programme demonstrates that a structured, habituation-based approach effectively reinforces Islamic character formation in children at the grassroots level.